The democratic soul : Spinoza, Tocqueville, and Enlightenment theology - Herold, Aaron L. (University of Pennsylvania Press, 2021)
"This book offers a fresh encounter with Enlightenment theology, one that can determine its integral connections to liberal democracy's foundations and its potential links to our current crisis. It asks whether the religious outlook the early modern tradition bequeathed us is truly at the root of our vulnerabilities, or (alternatively) whether it might not contain the basis for a richer, more robust, and higher-aiming liberal civic life. If it does turn out that modernity's theological basis contains big problems, and that these problems have come down to us in ways we now have trouble discerning, Herold argues that we will then need to examine the role a responsible and civically concerned political science can play in addressing our situation. That is what he aims to do in this book. Through a detailed analysis of Spinoza's Theologico-Political Treatise and Tocqueville's Democracy in America, he seeks to reveal not only the foundations of our moral hopes for liberalism and democracy but also the reasons why those hopes seem to be unfulfilled in ways we ourselves often have trouble grasping--and what we can do about it"--